Improving Four-Electrode Impedance Measurements by Numerical Simulations - Arbeiter, Nils; Pobner, Lucas; Schöbel, Lisa; Boccaccini, Aldo R.; Van Rienen, Ursula; Zimmermann, Julius (Proceedings of International Workshop on Impedance Spectroscopy, IWIS 2024, 2024)
The tissue dielectric properties are highly relevant for biomedical engineering applications. Four-electrode impedance measurements offer the possibility of measuring the actual tissue dielectric properties. Accurate measurement of these properties is essential for the development and optimisation of medical devices and treatments. Compared to other measurement approaches, four-electrode measurements are believed to be independent of electrochemical interface effects. We present numerical simulations using the finite element method of a commercial chip that can be used for four-electrode impedance measurements. With that, we establish means to validate experimental setups, characterise the setups regarding measurement ranges, facilitate the choice of measurement equipment and support the optimal placement of measurement electrodes, offering guidance for optimising experimental setups. With different simulation approaches regarding distributed or interface impedances, it is possible to gain insight into the underlying physical concepts. The validated chip allows accurate predictions for further experiments, including more than one material and dispersion.
CRIS-Team Scopus Importer:2025-04-01
Keywords: FEM simulations; four-electrode measurements; impedance spectroscopy; validation